2021
DOI: 10.1021/acsanm.1c00116
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer-Thick High-Entropy Alloy Nitride Al0.4Hf0.6NbTaTiZrN-Based Solar Selective Absorber Coatings

Abstract: Solar selective absorber coatings (SSACs), with the characteristics of efficient harvesting and conversion of solar energy into the heat work fluid, are considered to be one of the key components for the concentrating solar power (CSP) system. In this work, a nanometer-thick high-entropy alloy nitride Al 0.4 Hf 0.6 NbTaTiZrN-based SSAC is successfully deposited. The as-deposited coating exhibits a high solar absorptance (0.931) and a low emittance (0.064), which produces a high solar−thermal conversion efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Furthermore, the performance of the near-perfect MA was compared with that of some previously developed absorbers in Table 2. As can be seen in Table 2, Wu et al designed a MA based on nanoporous W/SiO 2 film, which can obtain the η of 90.32% that is 2.52% lower than the 92.84% of the near-perfect MA when C = 1 and T abs = 373 K. 20 Wang et al reported an absorber using manganese-iron oxide nanoparticles, achieving the η of 89.30% that is 5.74% lower than the 95.04% of the present near-perfect MA under C = 1000 and T abs = 1023 K. 40 Niranjan et al studied a W/WAlSiN/SiON/SiO 2 multilayer, which can obtain the η of 89.50% that is 5.01% lower than the 94.51% of the near-perfect MA when C = 100 and T abs = 773 K. 41 He et al studied an absorber based on alloy nitride MoTaTiCrN nanofilms, obtaining the η of 86.90% that is 6.92% lower than the 93.82% of the near-perfect MA under C = 100 and T abs = 823 K. 42 Ye et al reported an absorber based on a tungsten sphere and cuboid array, which can achieve the η of 87.56% that is 0.81% lower than the 88.37% of the near-perfect MA when C = 100 and T abs = 1000 K. 43 Zhang et al designed a chimney-like absorber, which can obtain the η of 91.62% that is 1.83% lower than the 93.45% of the near-perfect MA when C = 1000 and T abs = 1200 K. 44 Li et al reported an absorber based on TiN particles, obtaining the η of 93.00% that is 1.12% lower than the 94.12% of the near-perfect MA when C = 1 and T abs = 373 K. 45 Zhao et al proposed a Al 0.4 Hf 0.6 NbTaTiZrN MA, which can achieve the η of 74.90% that is 20.45% lower than the 95.35% of the near-perfect MA under C = 100 and T abs = 673 K. 46 Raza et al designed an absorber using SiC–W nanoparticles, achieving the η of 82.68% that is 3.13% lower than the 85.81% of the near-perfect MA under C = 100 and T abs = 1050 K. 47 Qiu et al studied an absorber based on TiB 2 –ZrB 2 composite ceramic, which can obtain the η of 83.90% that is 10.61% lower than the 94.51% of the near-perfect MA when C = 100 and T abs = 773 K. 48 He et al reported a double-layer alloy nitride HfNbTaTiZrN absorber, obtaining the η of 90.10% that is 3.75% lower than the 93.85% of the near-perfect MA under C = 100 and T abs = 823 K. 49 The above mentioned results demonstrate that the photothermal conversion performance of the present near-perfect MA is better than some previously absorbers.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the performance of the near-perfect MA was compared with that of some previously developed absorbers in Table 2. As can be seen in Table 2, Wu et al designed a MA based on nanoporous W/SiO 2 film, which can obtain the η of 90.32% that is 2.52% lower than the 92.84% of the near-perfect MA when C = 1 and T abs = 373 K. 20 Wang et al reported an absorber using manganese-iron oxide nanoparticles, achieving the η of 89.30% that is 5.74% lower than the 95.04% of the present near-perfect MA under C = 1000 and T abs = 1023 K. 40 Niranjan et al studied a W/WAlSiN/SiON/SiO 2 multilayer, which can obtain the η of 89.50% that is 5.01% lower than the 94.51% of the near-perfect MA when C = 100 and T abs = 773 K. 41 He et al studied an absorber based on alloy nitride MoTaTiCrN nanofilms, obtaining the η of 86.90% that is 6.92% lower than the 93.82% of the near-perfect MA under C = 100 and T abs = 823 K. 42 Ye et al reported an absorber based on a tungsten sphere and cuboid array, which can achieve the η of 87.56% that is 0.81% lower than the 88.37% of the near-perfect MA when C = 100 and T abs = 1000 K. 43 Zhang et al designed a chimney-like absorber, which can obtain the η of 91.62% that is 1.83% lower than the 93.45% of the near-perfect MA when C = 1000 and T abs = 1200 K. 44 Li et al reported an absorber based on TiN particles, obtaining the η of 93.00% that is 1.12% lower than the 94.12% of the near-perfect MA when C = 1 and T abs = 373 K. 45 Zhao et al proposed a Al 0.4 Hf 0.6 NbTaTiZrN MA, which can achieve the η of 74.90% that is 20.45% lower than the 95.35% of the near-perfect MA under C = 100 and T abs = 673 K. 46 Raza et al designed an absorber using SiC–W nanoparticles, achieving the η of 82.68% that is 3.13% lower than the 85.81% of the near-perfect MA under C = 100 and T abs = 1050 K. 47 Qiu et al studied an absorber based on TiB 2 –ZrB 2 composite ceramic, which can obtain the η of 83.90% that is 10.61% lower than the 94.51% of the near-perfect MA when C = 100 and T abs = 773 K. 48 He et al reported a double-layer alloy nitride HfNbTaTiZrN absorber, obtaining the η of 90.10% that is 3.75% lower than the 93.85% of the near-perfect MA under C = 100 and T abs = 823 K. 49 The above mentioned results demonstrate that the photothermal conversion performance of the present near-perfect MA is better than some previously absorbers.…”
Section: Resultsmentioning
confidence: 99%
“…Alloy composed of five or more main elements is called high entropy alloys (HEAs), which is emerging as a new promising SSA material. It was reported that HEA containing transition metal elements (such as Ti, Ta, Hf, Mo, Cr, and Zr) have excellent thermodynamic and optical properties, such as AlCrTaTiZrN, [ 30 ] (AlCrTaTiZrRu)N 0.7 , [ 31 ] Al 0.4 Hf 0.6 NbTaTiZrN, [ 32 ] AlCrWTaNbTiN, [ 33 ] etc. These have been widely studied because of their excellent thermal stability.…”
Section: Recent Advances In Ssasmentioning
confidence: 99%
“…Zhao et al fabricated a nanometer-thick high-entropy alloy nitride Al 0.4 Hf 0.6 NbTaTiZrN-based SSAC onto 306 SS via reactive RF magnetron sputtering (Zhao et al, 2021). The asdeposited coating exhibits a high absorptance of 0.931 and a low emittance of 0.064.…”
Section: High-entropy Ceramic-based Solar Selective Absorbing Coatingsmentioning
confidence: 99%